Natranaerofaba carboxydovora gen. nov., sp. nov., an extremely haloalkaliphilic CO‐utilizing acetogen from a hypersaline soda lake representing a novel deep phylogenetic lineage in the class 'Natranaerobiia'. (30th September 2020) - Sorokin, Dimitry Y.; Diender, Martijn; Merkel, Alexander Y.; Koenen, Michel; Bale, Nicole J.; Pabst, Martin; Sinninghe Damsté, Jaap S.; Sousa, Diana Z.
Summary: An anaerobic enrichment with CO from sediments of hypersaline soda lakes resulted in a methane‐forming binary culture, whereby CO was utilized by a bacterium and not the methanogenic partner. The bacterial isolate ANCO1 forms a deep‐branching phylogenetic lineage at the level of a new family within the class ' Natranaerobiia '. It is an extreme haloalkaliphilic and moderate thermophilic acetogen utilizing CO, formate, pyruvate and lactate as electron donors and thiosulfate, nitrate (reduced to ammonia) and fumarate as electron acceptors. The genome of ANCO1 encodes a full Wood–Ljungdahl pathway allowing for CO oxidation and acetogenic conversion of pyruvate. A locus encoding Nap nitrate reductase/NrfA ammonifying nitrite reductase is also present. Thiosulfate respiration is encoded by a Phs/Psr‐like operon. The organism obviously relies on Na‐based bioenergetics, since the genome encodes for the Na + ‐Rnf complex, Na + ‐F1F0 ATPase and Na + ‐translocating decarboxylase. Glycine betaine serves as a compatible solute. ANCO1 has an unusual membrane polar lipid composition dominated by diethers, more common among archaea, probably a result of adaptation to multiple extremophilic conditions. Overall, ANCO1 represents a unique example of a triple extremophilic CO‐oxidizing anaerobe and is classified as a novel genus and species Natranaerofaba carboxydovora in a novel family Natranaerofabacea .